Factors Influencing the Interannual Variation in Biomass of Bottom-Cultured Yesso Scallop (Patinopecten yessoensis) in the Changhai Sea Area, China - Nan, Xueliang; Wei, Hao; Zhang, Haiyan; Nie, Hongtao (Frontiers in Marine Science, 2022)
Further understanding of how environmental factors affect interannual differences in scallop growth and developing an easily obtained parameter to indicate these differences could provide a scientific basis for the optimization of their aquaculture methods. In this study, through setting a growth scenario of uniformly sowing scallops of the same initial size in the Changhai sea area, the Yesso scallop culture ecosystem (YeSCE) model was used to simulate the growth of bottom-cultured Yesso scallop each year from December 1, 2006 to November 30, 2017. The results show that the annual growth rate in the northwest was higher than that in the southeast, and there were obvious high-value areas near the islands. The scallop biomass was significantly lower in 2009–2010 and reached its highest point in 2013–2014. Based on the match-mismatch conditions of the relationship of bottom water temperature, food availability, and Yesso scallop growth process, three factors of suitable growth days, restricted growth days, and food accumulation were extracted, and a multiple regression relationship was proposed with scallop biomass to explore the reasons affecting the interannual differences of scallop growth. We found that the anomaly of the contribution of suitable growth days and food accumulation for scallop growth was small, the interannual differences in scallop biomass were mainly regulated by restricted growth days in winter. The results of the present work implied that the interannual differences in restricted growth days in winter were well related to the air temperature in early winter. As the air temperature in early winter is easily obtained in practice, it could be used to predict the interannual growth of bottom-cultured scallops to improve aquaculture planning and management.